GEOSTATISTICAL ANALYSIS OF TOMATO FRUIT ROT AND DIVERSITY OF ASSOCIATED FUNGAL SPECIES - A. Hussain; S. W. Khan; S. Ali; F. Faiz; M. Hussain; A. Ali; Shams Ur Rahman; S. Qasim (Journal of Animal and Plant Sciences, 2020)
Tomato fruit rot caused by fungi is the most common postharvest problem. The fungi are responsible for spoilage of produce between harvest and consumption. This study analyzed the distribution of tomato fruit rot using descriptive as well as geostatistical techniques and diversity of associated fungal species. Descriptive statistics indicated that the rot incidence and severity ranged from 10.22-44.17% and 0.7 - 7.10 mm. Geostatistical techniques were used to predict the spatial dependency class. Results revealed that rot incidence data had a nugget/ sill ratio of 0.487 inferring moderate spatial dependence, whereas severity inferring weak spatial dependence with nugget/ sill ratio of 0.221. Furthermore, geostatistical analysis was also applied to examine spatial variability within-ﬁeld using semivariogram and kriged maps. The maps of current study showed spatial distribution of rot incidence and severity in the study area. These digital maps will be helpful to develop pre- and post-harvest management strategies against tomato fruit rot. A total of nine fungal species were isolated from infected tomato fruit namely; Geotrichum candidum, Alternaria alternata, Aspergillus flavus, Aspergillus niger, Bipolaris, Fusarium oxysporum, Rhizopus stolonifer, Culvularia lunata and Penicillum digitatum. Aspergillus flavus was dominating species (17.02%) followed by Fusarium oxysporum (14.89%) and Alternaria alternata (12.76%), while Culvularia lunata has the least occurrence (6.38%).This study provides information about post-harvest rotting fungi of tomato to the growers, extension workers and researchers in the district Gilgit.
Keywords: Tomato rot; distribution; GIS; geostatistics; associated fungi; Gilgit-Baltistan